Análisis con enfoque de SPG (Sistema de participación de garantías) agroecológico de los socios de la feria de la Mata a la Olla del cantón Latacunga, 2022. - Benavides Lamar, Héctor Andrés (2023)
This research aimed to analyze the guarantee participation systems (GPS) for 104 members of 'De la mata a la olla' fair partners in Latacunga canton. The proposed objectives were raising the producers' baseline and auditing the level of compliance based on the indicators proposed in the file that the SPG is based on.The research was descriptive with a qualitative-quantitative approach; it began with a zoning of each partner to make a graphic representation through a map projected in the ArcGis software; for the collection of information, we used the survey technique with a questionnaire as an instrument, for which socialization of the file was carried out to the partners belonging to the Mata a la Olla fair, the 104 producers were organized into sectors according to their place of origin. The results obtained after the information gathering determine that the lowest averages are accepted in the soil conservation component, while the agricultural species component is the one that presents the best standards; regarding the audit process, it was obtained that in San Buenaventura, there is 100% in transition; Aláquez there is 100% in transition; Belisario Quevedo there is 15.8% in the beginning, 78.9% transition and 5.3% agroecological; San Juan de Pastocalle with 6.7% in the beginning, 73.3 transitions and 20% agroecological; Guaytacama with 100% transition; Ignacio Flores with 38.8% in the beginning, 61.2% transition; Eloy Alfaro with 50% at the beginning and 50% transition; Betlemitas with 100% start. It is concluded that the producers of the fair should put more emphasis on the soil conservation component to increase their score and get to obtain the rank of agroecologist.